Innovative technologies in composite floating docks construction - Rashkovskyi, A. S.; Рашковский, А. С.; Ermakov, D. V.; Ермаков, Д. В.; Dong, Zhao; Дун, Чжао (My University, 2014)
The aim of the article is the familiarization with the developed innovative technologies in the construction of reinforced-concrete floating structures on the example of composite floating docks (reinforced-concrete pontoon, steel towers). The advantages of composite floating structures compared with all-metal ones and the results of reinforced-concrete ele-ments optimization which provided the minimum usage of steel have been given. The new materials for floating reinforced-concrete structures are developed. This structures are based on the modified concrete which provides their long time performance and exploitation dura-tion in the sea water. Such structures can perform up to 70–80 years that is more than steel ones in 1.5–2 times. The construction technology of composite floating docks which have almost unlimited lifting force and sizes from separated large parts with further caissonless jointing of reinforced-concrete pontoon on length and width afloat without submerged-technical works is developed. This technology can be used both at the building yard and at the place of its exploitation and the technology does not have any analogues in the worldwide practice of dock construction. The research results can be used for design and construction of any floating structures exploited in the sea water.
Инновационные технологии в строительстве композитных плавучих доков
Rashkovskyi, A. S. Innovative technologies in composite floating docks construction = Инновационные технологии в строительстве композитных плавучих доков / A. S. Rashkovskyi, D. V. Ermakov, Dong Zhao// Shipbuilding & Marine Infrastructure. – 2014. – № 2 (2). – P. 93–102.
Keywords: floating dock; steel-concrete pontoon; technology of pontoon merging; competi-tive docks; the range of docks; плавучий док; технология сращивания понтона; железобетонный понтон; конкурентоспособные доки; конструктивный ряд доков